Die triomf van "n post-skolastieke mistiek oor skolastieke lojalisme: Gersonius versus Ruusbroec (postuum), 1399 - Beukes, Johann (HTS teologiese studies, 2020)
The triumph of a post-scholastic mysticism over scholastic loyalism:Gerson versus Ruusbroec (posth.), 1399. This article provides an introduction to the thought of the Flemish-Brabant 14th-century mystical thinker, Jan van Ruusbroec, with special attention to the explosion in the niche research from 1981 (with the publication of the first volume of the Ruusbroec Opera Omnia) to 2017 (regarding the specialised outputs of the Ruusbroec Institute at the University of Antwerp). Ruusbroec is presented as a ‘post-scholastic’ thinker, who in an idiosyncratic way, transcended the high-scholastic aspirations of absolute clarity and certainty about God and human existence. His thought is contextualised within a polemical, posthumous context, namely the attempt of the chancellor of the University of Paris at the time, John Gerson, to get Ruusbroec’s text‘, ‘Die geestelike brulocht’ declared as heresy and Ruusbroec himself as a heretic in the year 1399 AD, 18 years after Ruusbroec’s death. The attempts of Ruusbroec’s young colleagues at the modest monastery of Groenendaal, confronting and rearguing Gerson on this issue, are thoroughly explored. The fact that neither ‘Die geestelike brulocht’ nor Ruusbroec himself could eventually be effectively challenged by the high-powered Gerson, is presented as an example of the inherent potential of ‘post-scholasticism’ to contribute to the progression that eventually manifested itself as the ‘new world’, the Renaissance. No one won or lost this posthumous battle: but Gerson certainly did not win it. This is a remarkable note in, even a ‘triumph’ for, the archives of the small Augustinian monastery in Groenendaal, consisting of subtle ‘Augustinian’ monks, who had little more than a dedicated passion for Ruusbroec’s mysticism (and an undergraduate in theology at the University of Paris) on their side. A hermeneutic interpretation of the events of 1399 is henceforth presented, to indicate that within the socio-political turmoil of European societies in the 14th century, there were still places (and thinkers, such as Ruusbroec), where people were able to find ‘rest in God’ – as there should be today.